Role of cytokines, NO, and H2O2 on the immunopathology of Leptospirosis in genetically selected mice - M. Marinho; H. Langoni; S. L. Oliveira; V. M. F. Lima; J. R. Peiró; S. H. V. Perri; R. Carreira (Journal of Venomous Animals and Toxins including Tropical Diseases, 2005)
Immune response to leptospirosis is mainly humorally mediated, and involves opsonization of leptospires for phagocytosis by macrophages and neutrophils. However, some aspects are still unknown. For a more detailed analysis of the cellular immune response to leptospirosis infection, trials were carried out in order to determine the hydrogen peroxide and nitric oxide (H2O2 and NO) production stimulated or not by Interferon-gamma. The participation of some specific cytokines, such as Tumor Necrosis Factor-alpha (TNF-alpha); Interferon-gamma (IFN-gamma); Interleukin-6 (IL-6); and Interleukin-4 (IL-4), in the immunopathology of this infection was also investigated. For this purpose, we analyzed the supernatant from peritoneal macrophage cell culture and the splenic cells of mice genetically selected as High (H) and Low (L) antibody producers, and inbred Balb/c mice infected with Leptospira interrogans serovar icterohaemorrhagiae. The IL-6 production varied from release peaks to inhibition in H, L, and Balb/c mice. Similar behavior was observed for IL-4, produced only by H and Balb/c mice. The three strains presented constant and elevated production of TNF-alpha until day 14, suggesting its effective participation in the initial phase of the infection. Meanwhile, all the three strains presented a constant and irregular IFN-gamma production, with release peaks between the 7th and 14th days in L mice. The H and Balb/c mice strains presented a higher tendency to Th2 response pattern, whereas L mice tended towards Th1 response.